Numerical study of morphological response of the sandy bed after tsunami-like wave overtopping an impermeable seawall. (15th August 2019) - Zhao, Enjin; Qu, Ke; Mu, Lin
Abstract: In recent tsunami events, as those happened in Japan in 2011 and in Indian Ocean in 2018, many ocean and coastal structures have been damaged tremendously. Seawall is one of the most important coastal infrastructures to withstand the tsunami and reduce the harm of the tsunami. The investigation of the interaction between the seawall and tsunami wave is a significant aspect to reveal the influence mechanism of the tsunami and decrease the tsunami risk. With this scope, the effect of tsunami-like wave on the seawall and sandy bed is analyzed by the coupling model of fluid and sediment modules. The free surface of the fluid module is captured using VOF technology. The sediment transport module contains the calculation methods of sediment drift, precipitation and suspension. In order to guarantee the accuracy of the calculation, this model is verified through the comparison between the numerical and experimental data. The tsunami-like wave generated according to the record in the Iwate station in 2011 Japan tsunami event is used to impinge the seawall. After the wave overflows the seawall, the sandy bed is scoured. Based on the force on the seawall and scour hole profile, the damage energy of the tsunami-like wave is assessed. Besides, the influence of solitary wave on the seawall and sandy bed is also studied for comparison. It is found that the coastal scour caused by the tsunami-like wave is more serious than solitary wave. With the increase of wave height, the forces on the seawall and the scour depth increase. When the seawall is widened, the effect of the seawall on the wave reflection is enhanced, however, much water still can pass over the seawall. The outcome of this analysis can provide a reference for the construction of the seawall and improve the understanding of the interaction between the tsunami wave and the marine infrastructures. Highlights: A real-world tsunami-like wave is used as the generation of tsunami wave instead of solitary wave. Different effects of the solitary and real-world tsunami-like waves on the seawall and sandy bed are compared in detail. The forces on the seawall and the scour of sandy bed under different extreme waves are systematically investigated. Effects of different seawalls on the interaction among tsunami-like wave, seawall and sandy bed are analyzed.